Rājyābhisheka-candrikā : Śrī Pratapasiṃha Gāyakavāḍa, adhipati mājī sãsthāna Baḍodẽ, yāñcya rājyābhishekācyā vrttāntasaha prācīna Ārya rājyasãsthā, rājyābhishjekavidhi va pūrvāñcya rājyābhishekācyā hakīgatī varṇana karaṇārā grantha - Āpaṭe, Dājī Nāgeśa, b. 1888 (SAMP early 20th-century Indian books project, 1950)
Description of the coronation of Pratapasiṃha Gāyakavāda, Maharaja of Baroda.